Frequent mismatch-repair defects link prostate cancer to Lynch syndrome. Issue 1 (December 2016) - Dominguez-Valentin, Mev; Joost, Patrick; Therkildsen, Christina; Jonsson, Mats; Rambech, Eva; Nilbert, Mef
Abstract Background A possible role for prostate cancer in Lynch syndrome has been debated based on observations of mismatch-repair defective tumors and reports of an increased risk of prostate cancer in mutation carriers. Potential inclusion of prostate cancer in the Lynch syndrome tumor spectrum is relevant for family classification, risk estimates and surveillance recommendations in mutation carriers. Methods We used the population-based Danish HNPCC-register to identify all prostate cancers that developed in mutation carriers and in their first-degree relatives from 288 Lynch syndrome families. The tumors were evaluated for clinicopathologic features and mismatch-repair status, and the cumulative risk of prostate cancer was determined. Results In total, 28 prostate cancers developed in 16 mutation carriers and in 12 first-degree relatives at a median age of 63 years. The majority of the tumors were high-grade tumors with Gleason scores 8–10. Prostate cancer was associated with mutations inMSH2, MLH1 andMSH6 with loss of the respective mismatch repair protein in 69 % of the tumors, though a MSI-high phenotype was restricted to 13 % of the tumors. The cumulative risk of prostate cancer at age 70 was 3.7 % (95 % CI: 2.3–4.9). Conclusion We provide evidence to link prostate cancer to Lynch syndrome through demonstration of MMR defective tumors and an increased risk of the disease, which suggests that prostate cancer should be considered in the diagnostic work-up of Lynch syndrome.